Sexual Gratification as an Expanded Form of Corruption Crime Under Indonesian Positive Law - Hutagalung, Jantarda Mauli; Saputri, Adhalia Septia (Devotion : Journal of Research and Community Service, 2024)
Along with its development, the category of sexual gratification emerged which received a lot of attention from the public and law enforcement officials. This sexual satisfaction is different from the satisfaction we know in general. The difference lies in the object. Sexual gratification is a form of degrading women's dignity. In Indonesia, sexual gratification has not been explicitly regulated. Therefore, this research will discuss the regulation of sexual gratification based on positive law in Indonesia and the evidence. From the results of the analysis it is known that sexual gratification can be included in the provisions of Article 12 B paragraph 1 of Law 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. This can be found in the phrase "other facilities" where "facilities" themselves are defined as the means used to facilitate an implementation. Therefore, the use of sexual service facilities with the aim of achieving all desires is the intention of the party providing satisfaction. Proof of the existence of sexual gratification in eradicating corruption in Indonesia is based on criminal procedural law which refers to the Criminal Procedure Code (KUHAP) in Article 184 paragraph (1) and Article 26A of Law Number 20 of 2001 Jo. Law Number 31 of 1999 uses a reverse or balanced evidentiary system where the burden is on the Public Prosecutor and the defendant to provide evidence of the criminal act of sexual gratification for which the defendant is charged.